Parental experience of transition from a paediatric intensive care unit to a general ward: A qualitative study. (7th July 2022) - Ji, Jianlin; Yang, Liling; Yang, Hanlin; Jiang, Yan; Tang, Ping; Lu, Qunfeng
Abstract: Aim: We aim to explore parental experience in transitioning from a paediatric intensive care unit to a general ward and to investigate parental involvement in caring for their critical illness children. Background: Parents have a major responsibility in caring for seriously ill children, but nursing staff fail to meet the expectations of parents regarding nursing care. Few studies have investigated the challenges and needs of Chinese parents during the transition from paediatric intensive care unit to general ward. Methods: Semi‐structured interviews were conducted with 24 parents of children with critical illness in a paediatric hospital in Shanghai, mainland China to explore their views. Transcripts were entered into NVivo. Framework analysis was used to analyse the qualitative data. Results: Four themes were identified by data analysis: changes in the child during post paediatric intensive care unit periods; experiencing a wide range of emotions; factors involved in the transition; and suggestions for improving transitional care. Conclusions: Due to the unmet needs of parents, a more flexible visiting policy and social media support were highly desirable. Getting accurate information, establishing family integrated care, and strengthening ward‐based critical support services were also listed as important needs of parents caring for critically ill children. Implications for Nursing Management: A profound understanding of parental experiences during the transitional period can help nursing staff to assess the effects on children and their families, improve ward‐based intensive care, support parental participation, and improve visitation policies. Based on these findings, nurse managers can develop reasonable intervention programmes in order to improve nursing quality and patient outcomes